FATORES ASSOCIADOS AO ÓBITO EM GESTANTES E PUÉRPERAS INDÍGENAS E NÃO INDÍGENAS POR SÍNDROME RESPIRATÓRIA AGUDA GRAVE PELA COVID-19, NO BRASIL - Adryelle Katheline D'Elia de Moura (2023)
COVID-19 is a disease caused by the new coronavirus and has become a devastating threat to the health of the world's population, with Severe Acute Respiratory Syndrome (SARS-Cov- 2,) as its most serious form. Pregnant and postpartum women are among the risk groups, since the physiological changes during pregnancy and postpartum increase the risk of infections and make them susceptible to SARS. Indigenous peoples are also classified as a risk group and are the target of serious conditions, mainly respiratory, due to situations of social and health vulnerability. This research aimed to analyze the association between sociodemographic determinants, comorbidities, symptoms and characteristics of hospitalization with the outcome of indigenous and non-indigenous pregnant and puerperal women hospitalized for SARS by COVID-19, in Brazil. The study is cross-sectional, quantitative and retrospective, with secondary data, extracted from the Brazilian Obstetric Observatory Database (OOBr), of pregnant and postpartum women of reproductive age (between 10 and 49 years), hospitalized for SARS by COVID-19, classified as in indigenous and non-indigenous race/skin color (white, black, brown and yellow women), in the period from the 9th epidemiological week of 2020 to the 35th week of 2022. The variables with the outcome were analyzed using the chi- test. square and 95% confidence interval (95% CI). Logistic regression was performed to identify factors associated with death in indigenous pregnant and postpartum women. In general, the factors associated with death were presented by pregnant women in the 3rd trimester, aged 20 to 34 years, living in the urban/peri-urban area and in the Northeast region, without comorbidities and O2 saturation < 95%, in addition to dyspnea and requiring hospitalization in ICU, using invasive ventilatory support. When comparing the cases of death between indigenous and non-indigenous women, a significant statistical difference could be observed with more vulnerability among indigenous women in the variables condition (pregnant/postpartum woman), age group, education, area of residence, region of residence and comorbidities. It is noteworthy that among indigenous women, living in a rural area increases their chance of dying by thirty-three times when compared to indigenous people living in urban/peri-urban areas. Living in the North and Midwest regions, they increase by more than ten times when compared to the South/Southeast. It is concluded that the pandemic has exacerbated and deepened social and ethnic-racial inequalities in Brazil, making specific efforts necessary to guarantee qualified and timely care for this population. Descriptors: Health of indigenous populations; Pregnant women; Postpartum Period; COVID- 19; Family Health Strategy.